2003
DOI: 10.1152/ajpheart.00425.2002
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dynamics in the failing heart: restoration by β-adrenergic receptor blockade

Abstract: Changes in calcium (Ca2+) regulation contribute to loss of contractile function in dilated cardiomyopathy. Clinical treatment using β-adrenergic receptor antagonists (β-blockers) slows deterioration of cardiac function in end-stage heart failure patients; however, the effects of β-blocker treatment on Ca2+ dynamics in the failing heart are unknown. To address this issue, tropomodulin-overexpressing transgenic (TOT) mice, which suffer from dilated cardiomyopathy, were treated with a nonselective β-receptor bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
25
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 52 publications
5
25
0
Order By: Relevance
“…This may be due to increased myofibrillar content, as previously reported by Carabello and coworkers (18). In addition, ␤ 1 -RB improved Ca 2ϩ transients, a finding that is consistent with studies in chronic dilated cardiomyopathy in humans (6) and in tropomodulin-overexpressing transgenic mice (12), where ␤ 1 -RB restored Ca 2ϩ handling and improved Ca 2ϩ transients in cardiomyocytes from failing hearts. Interestingly, Iso-induced Ca 2ϩ transients did not differ from normal in untreated and ␤ 1 -RB-treated MR dogs.…”
Section: Discussionsupporting
confidence: 88%
“…This may be due to increased myofibrillar content, as previously reported by Carabello and coworkers (18). In addition, ␤ 1 -RB improved Ca 2ϩ transients, a finding that is consistent with studies in chronic dilated cardiomyopathy in humans (6) and in tropomodulin-overexpressing transgenic mice (12), where ␤ 1 -RB restored Ca 2ϩ handling and improved Ca 2ϩ transients in cardiomyocytes from failing hearts. Interestingly, Iso-induced Ca 2ϩ transients did not differ from normal in untreated and ␤ 1 -RB-treated MR dogs.…”
Section: Discussionsupporting
confidence: 88%
“…We found overexpression of WT RAFTK/pyk2 caused dramatic changes in myofibril organization consistent with a role in reorganization of focal adhesions and cytoskeleton and demonstrated that RAFTK/pyk2 is activated in dilated cardiomyopathy (7). Chronic elevation of intracellular calcium in cardiomyocytes of failing hearts (8,9) is presumably responsible for RAFTK/pyk2 activation, which then leads to redistribution and altered phosphorylation of paxillin (7).…”
supporting
confidence: 57%
“…The precipitating stimulus of chronically impaired calcium handling promotes maladaptive remodeling via activation of calcium-dependent signaling cascades (4,5) with chronic elevation of calcium influx leading to hypertrophy and heart failure in transgenic mice (6). Earlier work from our group demonstrated activation of related adhesion focal tyrosine kinase (RAFTK, also known as pyk2) signaling in cultured cardiomyocytes treated with ionomycin (7) as well as a murine model of dilated cardiomyopathy exhibiting chronic elevation of intracellular calcium levels (8,9). Concurrent with RAFTK/pyk2 activation, heart samples from cardiomyopathic mice showed enhanced paxillin phosphorylation (7).…”
mentioning
confidence: 99%
“…With respect to established pharmacological treatments in AF, our results might explain a part of the antiarrhythmic effect of ␤-blockers, which work upstream of CaMKII and which have been shown to reduce hyperphosphorylation of the RyR2 and reduce SR Ca 2ϩ leak. 45,46 Sources of Funding …”
Section: Summary and Perspectivesmentioning
confidence: 99%